PENGAJARAN PENDIDIKAN AGAMA KRISTEN TENTANG KARUNIA BAHASA ROH DALAM 1 KORINTUS 12:8-10 DI GPDI EFRATA DEPOK - Sihite, Jelita; Hizkia Chrisman El-Shaddai (THEOSOPHIA: Jurnal Teologi dan Pendidikan Kristiani, 2025)
In contemporary churches, misunderstandings regarding spiritual gifts often occur, where supernatural phenomena are frequently emphasized over Biblical truth, alongside a tendency for congregations to prioritize specific gifts such as healing. This study aims to provide a correct theological understanding of spiritual gifts according to the Apostle Paul's teaching in 1 Corinthians 12:8-10, to establish correct theology within the congregation. The method used in this research is qualitative with a library research approach, collecting and analyzing information from relevant written sources. The results show that the word "gift" (pneumatikon) refers to things originating from the Holy Spirit, not human ability. Paul describes various gifts—such as the word of wisdom, knowledge, faith, healing, miracles, prophecy, discerning of spirits, tongues, and their interpretation—as manifestations originating from the same Spirit. It is concluded that the primary purpose of these gifts is not for personal pride or a display of power, but rather granted for the common good to build unity and equip the body of Christ.